Segmented Network Coding for Stream-Like Applications in Delay Tolerant Networks - Deze Zeng; Song Guo; Hai Jin; Leung, V. (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011, 2011)
Delay/Disruption Tolerant Network (DTN) differs from the conventional networks in that it has no continuous or contemporaneous connections among wireless nodes. Its inherent characteristic of intermittent connections makes existing routing solutions hardly to be applied directly. Epidemic routing using random linear network coding has been studied and proved as an efficient way for light data delivery. In this paper, we propose a pipelined segmented network coding approach using double buffer to provide best-effort services for bulk or stream-like data dissemination in DTNs. Simulations were conducted to verify its performance in terms of packet delivery ratio and throughput. Several other interesting findings are also observed.